Analisis nilai profil pelajar pancasila dalam teks cerita fiksi pada buku siswa bahasa indonesia kelas 4 SD kurikulum merdeka - Agnes Dinar Nugraheni; Retno Winarni; Supianto Supianto (Universitas Sebelas Maret, 2024)
This research aims to analyze and describe the value of the Pancasila Student Profile found in fictional story texts in the Indonesian Language Student Book for Class 4 Elementary School Merdeka Curriculum. This research uses a non-experimental research design, namely research carried out without any intervention or treatment (trial) on the research subjects. The approach used is descriptive quantitative with content analysis research methods, while the data analysis technique used is a hermeneutical approach. The conclusion of this research is that the six dimensions of the Pancasila Student Profile Values have appeared in 12 fiction story text titles in the Indonesian Language Student Book for Class 4 SD Merdeka Curriculum. The mutual cooperation dimension has the highest percentage and frequency of occurrence, while the global diversity dimension has the lowest percentage and frequency of occurrence. Thus, these fictional stories are suitable to be used as a medium to instill Pancasila Student Profile Values, especially for elementary school students.